Therapeutic Effect of Cardiac Exercise Rehabilitation Program Based on Cardiopulmonary Exercise Test on Patients with Stable Coronary Heart Disease Complicated with Hypertension - TONG Yiman; GAO Min; WANG Xinyu; CAO Yuhan; CHEN Wei (康复学报)
ObjectiveTo observe the effect of cardiac exercise rehabilitation program based on cardiopulmonary exercise testing (CPET) on patients with stable coronary heart disease complicated with hypertension.MethodsA total of 80 patients with stable coronary artery disease complicated with hypertension in the Xuzhou Central Hospital from February to September 2023 were randomly divided into control group and observation group, with 40 cases in each group. The control group received routine medication for 12 weeks. The observation group received cardiac exercise rehabilitation program based on CPET in addition to the treatment of the control group, including aerobic exercise and resistance training, once every other day, 3 times a week for 12 weeks. Before and after treatment, CPET was used to evaluate cardiac autonomic function [such as rest heart rate (HRrest), rest systolic blood pressure (SBPrest), rest diastolic blood pressure (DBPrest), peak heart rate (HRpeak), peak systolic blood pressure (SBPpeak), peak diastolic blood pressure (DBPpeak), heart rate recovery from the 1st to 6th min (HRRt)]. CPET was used to evaluate cardiopulmonary function and exercise ability [peak metabolic equivalent (METspeak), peak work (Workpeak), peak oxygen pulse (VO2/HRpeak), peak oxygen uptake (VO2 peak), anaerobic threshold (AT) and carbon dioxide ventilation equivalents slope (VE/VCO2 slope)]. The 36-item short-form health survey (SF-36) was used to evaluate quality of life. Pittsburgh sleep quality index (PSQI) was used to evaluate sleep quality.ResultsCompared with that before treatment, SBPrest, DBPpeak, HRrest, HRpeak and VE/VCO2 slope in the observation group decreased significantly after treatment, HRR1-HRR6, VO2 peak, AT, VO2/HRpeak, METspeak, Workpeak, SF-36 scores (physical functioning, role physical, bodily pain, general health, social functioning and mental health) increased significantly, PSQI score decreased significantly (P<0.05). Compared with the control group, SBPrest, DBPpeak, HRrest and VE/VCO2 slope in the observation group were significantly lower after treatment, HRR1-HRR4, VO2 peak, AT, VO2/HRpeak, METspeak, Workpeak, SF-36 scores (physical functioning, role physical, bodily pain, general health, social functioning and mental health) were significantly higher after treatment (P<0.05), PSQI score decreased significantly (P<0.05).ConclusionThe cardiac exercise rehabilitation program based on CPET can improve cardiac autonomic function, cardiopulmonary function, exercise ability, sleep and quality of life of patients with stable coronary heart disease complicated with hypertension, which is recommended for clinical application.